Inductive algebras for the affine group of a finite field - Sharma P.; Vemuri M.K. (My University, 2025)
Each irreducible representation of the affine group of a finite field has a unique maximal inductive algebra, and it is self-adjoint. © 2022, African Mathematical Union and Springer-Verlag GmbH Deutschland, ein Teil von Springer Nature.